Artificial neural network for solving the nonlinear singular fractional differential equations. Issue 1 (31st December 2023) - Althubiti, Saeed; Kumar, Manoj; Goswami, Pranay; Kumar, Kranti
Abstract : This paper proposes an artificial neural network (ANN) architecture for solving nonlinear fractional differential equations. The proposed ANN algorithm is based on a truncated power series expansion to substitute the unknown functions in the equations in this approach. Then, a set of algebraic equations is resolved using the ANN technique in an iterative minimization process. Finally, numerical examples are provided to demonstrate the usefulness of the ANN architectures. The results verify that the suggested ANN architecture achieves high accuracy and good stability.